Rjasta kozarka Tadorna ferruginea - Bordjan, Dejan (Acrocephalus, 2018)
One observed on 23 Apr 2018 on Medvedce water reservoir (NE Slovenia). This is the second observation for the site and a rare one for Slovenia; accepted by the Slovenian Rarities Committee (Category C5)
Keywords: ornitologija; ptice; rjasta kozarka; Tadorna ferruginea